ChemInform Abstract: Synthesis and Properties of Lanthanide Ruthenium(III) Oxide Perovskites. Issue 47 (6th November 2014) - Sinclair, Alexandra; Rodgers, Jennifer A.; Topping, Craig V.; Misek, Martin; Stewart, Ross D.; Kockelmann, Winfried; Bos, Jan‐Willem G.; Attfield, J. Paul
Abstract A series of LnRuO3 perovskites (Ln: La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Y) is synthesized from stoichiometric mixtures of Ru, RuO2, and Ln2O3 at a pressure of 10 GPa for Ln: Pr, Nd, Sm, and 11 GPa for Ln: Eu, Gd, Tb, Dy, Ho, Y (1200 °C, 15 min).